2018
DOI: 10.4220/sykepleienf.2018.65521
|View full text |Cite
|
Sign up to set email alerts
|

Uklare rammer gjør det vanskelig å ivareta barn som pårørende

Abstract: Helsepersonell som arbeider med psykisk syke eller rusmisbrukende pasienter som har barn, er utrygge i rollen. Dermed blir det tilfeldig hvilken hjelp barna får .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…2,3,21,22 However, despite good intentions, willingness, and a favorable law, studies have shown that it is not easy for health professionals to pay attention to their adult patients' children. 6,7,[23][24][25][26][27][28][29] One study reported that although general practitioners are in a good position to help children as next of kin, these children easily remain invisible in the consultation with their parents. 6 Support to a child who is burdened as next of kin depends often not on careful consideration of what is best for the patient and the child in the long run, but more on short-term convenience reasons.…”
Section: Introductionmentioning
confidence: 99%
“…2,3,21,22 However, despite good intentions, willingness, and a favorable law, studies have shown that it is not easy for health professionals to pay attention to their adult patients' children. 6,7,[23][24][25][26][27][28][29] One study reported that although general practitioners are in a good position to help children as next of kin, these children easily remain invisible in the consultation with their parents. 6 Support to a child who is burdened as next of kin depends often not on careful consideration of what is best for the patient and the child in the long run, but more on short-term convenience reasons.…”
Section: Introductionmentioning
confidence: 99%